Context-dependent cheating: experimental evidence from 16 countries (2012)
Policy makers use several international indices that characterize countries according to the quality of their institutions. However, no effort has been made to study how the honesty of citizens varies across countries. This paper explores the honesty among citizens across sixteen countries with 1440 participants. We employ a very simple task where participants face a trade-off between the joy of eating a fine chocolate and the disutility of having a threatened self-concept because of lying. Despite the incentives to cheat, we find that individuals are mostly honest. Further, international indices that are indicative of institutional honesty are completely uncorrelated with citizens' honesty for our sample countries.